Peran Koperasi Wanita “SUMBER JAYA” Dalam Meningkatkan Perekonomian Wanita - Irmawati, Rikha; Choiriyah, Ilmi Usrotin (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
The economic condition of society in general, especially women, is a very important factor in empowering society in the economic sector. Economic empowerment is carried out to reduce poverty rates and increase welfare to develop women to be more productive so that they can increase the level and standard of living of women and improve family welfare.